Comparative study of CAD/CAM reconstruction and miniplates for patient-specific fixation in LCL-type mandibular reconstruction - Lampert, Philipp; Fenske, Jakob; Wüster, Jonas; Koerdt, Steffen; Kreutzer, Kilian; Ruf, Philipp; Checa, Sara; Heiland, Max; Steffen, Claudius; Rendenbach, Carsten (Frontiers in Oncology, 2024)
Objective: Miniplates offer superior clinical handling and facilitate postoperative removal after mandibular reconstruction but unfavorable load distribution under high stress has been shown. This study aimed to compare the clinical outcome of patient-specific 3D-printed (PS-3D) titanium miniplate with reconstruction plate fixation in three-segmental LCL-type reconstructions for the first time. Methods: Patients undergoing three-segmental LCL-type mandibular reconstruction after malignant tumor resection between April 2017 and July 2023 were analyzed in a retrospective single-center study. Inclusion criteria were primary reconstruction using a fibula free flap and PS-3D titanium mini- or reconstruction plate fixation. Complication rates were recorded and analyzed within 6 months after surgery using the N – 1 Chi2- and unequal variance t-test. Results: 38 patients (10 females, 28 males; mean age 61.4 ± 7.6 years) met the inclusion criteria. In 14 patients (36.8%) miniplates were used in the anterior region. Rates of fixation failure, plate exposure, incomplete osseous union, wound infection, soft tissue, and overall complications did not differ significantly between the two plate systems. Conclusion: Complication rates did not differ significantly between PS-3D mini- and reconstruction plates in three-segmental LCL-type mandibular reconstructions. Given their advantages in clinical handling and postoperative removal, PS-3D miniplates can be a viable alternative also in larger mandibular reconstructions.